Glycogen synthase kinase-3ß supports serotonin transporter function and trafficking in a phosphorylation-dependent manner - Varman, Durairaj Ragu (J Neurochem, 2020)
Serotonin (5-HT) transporter (SERT) plays a crucial role in serotonergic transmission in the central nervous system, and any aberration causes serious mental illnesses. Nevertheless, the cellular mechanisms that regulate SERT function and trafficking are not entirely understood. Growing evidence suggests that several protein kinases act as modulators. Here we delineate the molecular mechanisms by which glycogen synthase kinase-3ß (GSK3ß) regulates SERT. When mouse striatal synaptosomes were treated with the GSK3α/ß inhibitor CHIR99021, we observed a significant increase in SERT function, V(max), surface expression with a reduction in 5-HT K(m) and SERT phosphorylation. To further study how the SERT molecule is affected by GSK3α/ß, we used HEK-293 cells as a heterologous expression system. As in striatal synaptosomes, CHIR99021 treatment of cells expressing wild-type hSERT (hSERT-WT) resulted in a time and dose-dependent elevation of hSERT function with a concomitant increase in the V(max) and surface transporters due to reduced internalization and enhanced membrane insertion; silencing GSK3α/ß in these cells with siRNA also similarly affected hSERT. Converting putative GSK3α/ß phosphorylation site serine at position 48 to alanine in hSERT (hSERT-S48A) completely abrogated the effects of both the inhibitor CHIR99021 and GSK3α/ß siRNA. Substantiating these findings, overexpression of constitutively active GSK3ß with hSERT-WT, but not with hSERT-S48A, reduced SERT function, V(max), surface density, and enhanced transporter phosphorylation. Both hSERT-WT and hSERT-S48A were inhibited similarly by PKC activation or by inhibition of Akt, CaMKII, p38 MAPK or Src kinase. These findings provide new evidence that GSK3ß supports basal SERT function and trafficking via serine-48 phosphorylation.